2005
DOI: 10.1037/0882-7974.20.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Context Processing and Context Maintenance in Healthy Aging and Early Stage Dementia of the Alzheimer's Type.

Abstract: Declines in the ability to process context information may represent a fundamental mechanism of age-related cognitive changes. Two components of context processing--activation/updating and maintenance--were examined in a sample of healthy younger and older adults, along with individuals suffering from early stage dementia of the Alzheimer's type (DAT). All older adult groups showed context activation/updating impairments, whereas context maintenance was only impaired in the oldest adults (age>75 years) and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
217
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(258 citation statements)
references
References 61 publications
35
217
2
4
Order By: Relevance
“…1). These imaging-based age differences are consistent with prior behavioral studies, in which older adults exhibited smaller cue-based expectancy effects but also larger probe-related interference effects than younger adults (7)(8)(9).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…1). These imaging-based age differences are consistent with prior behavioral studies, in which older adults exhibited smaller cue-based expectancy effects but also larger probe-related interference effects than younger adults (7)(8)(9).…”
supporting
confidence: 80%
“…Active maintenance of this frequently updated task goal information is required to bridge the delay between cue and probe presentation. In a series of behavioral studies, it has been shown that the AX-CPT task provides sensitive and specific indices of cognitive control function (7)(8)(9). Likewise, neuroimaging studies have reliably demonstrated the presence of lateral PFC activity related to the active maintenance of task goals during AX-CPT performance (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were instructed to press the target button only when a specific probe item, X, occurred immediately following a particular contextual cue, A (hence the "AX" in the task name). Target AX trials occur with high frequency (70%), creating specific expectancies and response tendencies that can be examined, such as on AY trials (10%) that feature the usually reliable cue A but not the X probe, and on BX trials (10%) that have the X probe without the necessary A cue.Relative performance on these two types of nontarget trials, compared with the additional BY nontarget control condition (10%), provides an index of two types of cognitive control strategy: proactive and reactive control (for more information on the dual mechanisms of control theory, see Braver, Gray, & Burgess, 2007;Braver, Satpute, Rush, Racine, & Barch, 2005). Proactive control involves utilizing actively maintained context information to prime response selection.…”
mentioning
confidence: 99%
“…Furthermore, participants may be strategy focused, suggesting ways to deal with the problem without considering the underlying logic of this (Renger and Hurley 2006) typifying many of the difficulties with the early stages of intervention development, where the risk is that intervention components are included without a clear underlying rationale (Webb et al 2010). Our research concentrates on people in the early stages of dementia, for whom logical thinking and working memory remain largely unimpaired (Pasquier 1999;Braver et al 2005) and visual cognition is generally preserved (Morris et al 2001), supporting the use of this type of logic mapping method. Guidance on conducting research with people with dementia suggests a non-judgmental stance, accepting what participants say, building rapport and working to make the participant feel valued (Hellström et al 2007); this guidance was followed.…”
Section: Discussionmentioning
confidence: 99%